2013
DOI: 10.1089/apc.2012.0348
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Nominated, Community-Based HIV Treatment Supporters: Patient Perspectives, Feasibility, Challenges, and Factors for Success in HIV-Infected South African Adults

Abstract: This study aimed to characterize the experience of having a treatment supporter among HIV-infected South African patients enrolled in a randomized controlled trial that compared the efficacy of patient-nominated treatment supporters administering partial directly observed antiretroviral therapy (DOT-ART) versus selfadministered ART (Self-ART). Results of the parent study showed no virologic or sustained immunologic differences between groups, but revealed a significant survival benefit among the DOT-ART group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 29 publications
(29 reference statements)
3
43
0
Order By: Relevance
“…These findings are consistent with the importance and role of social support for PLHIV in other sub-Saharan Africa countries, including Ethiopia, Lesotho, South Africa, Tanzania, and Uganda. [22][23][24][25][26][27] The majority of social support received by PLHIV in this study was instrumental, followed by emotional and informational/appraisal support. This differs from historical research conducted in the United States in which emotional support was the most common attribute and believed to be the most important.…”
Section: Discussionmentioning
confidence: 81%
“…These findings are consistent with the importance and role of social support for PLHIV in other sub-Saharan Africa countries, including Ethiopia, Lesotho, South Africa, Tanzania, and Uganda. [22][23][24][25][26][27] The majority of social support received by PLHIV in this study was instrumental, followed by emotional and informational/appraisal support. This differs from historical research conducted in the United States in which emotional support was the most common attribute and believed to be the most important.…”
Section: Discussionmentioning
confidence: 81%
“…Such community-based interventions are likely to have more impact since they tend to involve trained community health workers, peers, volunteers, or patient’s own social network members (e.g., family and friends) who assist with ART adherence counseling and support. In addition, there is evidence that they may provide material, instrumental, and emotional support, as well as promote other healthy behaviors, such as decreased alcohol and drug use, leading to better health outcomes—including survival [14, 24, 29, 32]. Furthermore, enhancing certain aspects of the patient–supporter relationships—such as trust, supporter availability, communication, reciprocity of support, and medication assistance—in a manner consistent with patients’ expectations may help to optimize the relationship and its positive impact on patient health [14, 24, 70].…”
Section: Discussionmentioning
confidence: 99%
“…36 Health system capacity can be strengthened by ensuring autonomy over resources at lower levels; linking performance management interventions to facility-wide human resources management; and developing accountability systems to ensure that health workers and managers are responsible for their performance. 39,40 In addition, health systems should aim not only to provide knowledge to women but also to cultivate a supportive relationship that enables the women to apply the new knowledge to their daily lives, and come up with solutions to challenges to healthy daily routines. 36,41 This can only happen if patient-provider communication is improved at every stage of the continuum of care.…”
Section: Discussionmentioning
confidence: 99%
“…35 Strategies may also include patient-selected community-based treatment supporters to improve understanding of HIV and PMTCT particularly for newly diagnosed women. 21,39 Home visits by trained nurses or community health workers can be introduced to circumvent challenges such as expensive transport, long waiting lines, and discordant mother-infant clinic appointments, 36 and by extension enhance maternal and child outcomes. 39,41 Our finding that stigma and other psychosocial factors did not increase the odds of MTCT differs from prior studies in the region that have found that fears of HIV-related stigma and discrimination negatively impact service uptake and adherence at each step of the PMTCT cascade.…”
Section: Discussionmentioning
confidence: 99%